Occipital cortex dysgenesis with white matter changes due to mutations in Laminin a2 - Uluç Yiş; Vishal Dixit; Sedat Işıkay; Mert Karakaya; Figen Baydan; Gülden Diniz; İpek Polat; Semra Hız-Kurul; Sebahattin Çırak (The Turkish Journal of Pediatrics)
Laminin α2 related congenital muscular dystrophy is one of the most common congenital muscular dystrophies of childhood with or without clinical evidence of central nervous system involvement. It may be associated with significant white matter abnormalities resembling leukodystrophies. In this study, we elaborated on two cases with laminin α2 related congenital muscular dystrophy who had occipital cortex dysgenesis in addition to characteristic white matter abnormalities. Although laminin α2 related congenital muscular dystrophy with white matter abnormalities is known, the association with occipital cortex dysplasia has been not well recognized by clinical colleagues.